Emerging Metal Single Atoms in Electrocatalysts and Batteries. (18th August 2020) - Ma, Lianbo; Zhu, Guoyin; Wang, Dandan; Chen, Huixian; Lv, Yaohui; Zhang, Yizhou; He, Xiaojun; Pang, Huan
Abstract: Energy conversion and storage applications require highly stable and efficient electrocatalysts/electrodes to facilitate electrochemical reactions, but these materials commonly suffer from serious atom wastes and lower performances than the theoretical levels, which cannot meet the increasing demands of the green atomic economy, thereby limiting their practical applications. Recently, metal single atoms (SAs) have attracted tremendous attention owing to their merits of full atom utilization, unique electronic structures, tunable surface characteristics, and low costs. However, metal SAs usually have relatively low physical/chemical stabilities due to their high surface energy, which results in severe degradation of electrochemical performances. Novel synthetic strategies are developed for metal SAs with better stability and performance. In this review, these strategies will be introduced in the context of electrocatalysis and batteries. Specifically, the design concepts, synthesis approach properties, and applications of metal SAs will be discussed. Finally, the critical challenges and future perspectives of metal SAs are presented. This review aims to provide new insights for future work as well as the real‐world applications of metal SAs. Abstract : Metal single atoms (SAs) have attracted tremendous attention owing to their apparent merits. In this review, novel synthetic strategies for developing metal SAs with better stability and performance are summarized in electrocatalysts and batteries. It is believed that this review can provide new insights for future work as well as the real‐world applications of metal SAs.